2012
DOI: 10.1128/iai.05869-11
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Levels of Type III Secretion and Secreted Proteins with Fecal Shedding of Escherichia coli O157:H7 in Cattle

Abstract: The locus of enterocyte effacement (LEE) of Escherichia coli O157:H7 (O157) encodes a type III secretion system (T3SS) for secreting LEE-encoded and non-LEE-encoded virulence proteins that promote the adherence of O157 to intestinal epithelial cells and the persistence of this food-borne human pathogen in bovine intestines. In this study, we compared hha sepB and hha mutants of O157 for LEE transcription, T3SS activity, adherence to HEp-2 cells, persistence in bovine intestines, and the ability to induce chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Since QseBC-mediated quorum-sensing signaling in EHEC O157:H7 enhances flagellar gene expression and motility (13,15), which have indirectly been shown to be important for colonization (36,37), we compared the motility of the qseBC deletion mutant to those of the parental and the qseBCcomplemented mutant strains in the presence or absence of the QseBC-activating signaling molecule norepinephrine (NE). The phenotypic analysis of motility on soft-agar plates revealed that a deletion of the qseBC genes did not compromise bacterial motility.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since QseBC-mediated quorum-sensing signaling in EHEC O157:H7 enhances flagellar gene expression and motility (13,15), which have indirectly been shown to be important for colonization (36,37), we compared the motility of the qseBC deletion mutant to those of the parental and the qseBCcomplemented mutant strains in the presence or absence of the QseBC-activating signaling molecule norepinephrine (NE). The phenotypic analysis of motility on soft-agar plates revealed that a deletion of the qseBC genes did not compromise bacterial motility.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, we demonstrated the importance of motility and LEE for increased colonization of bovine intestines by EHEC O157:H7, since mutants expressing LEE at very high levels but compromised in bacterial motility were unable to colonize and persist in cattle intestines (37). Thus, regulatory pathways that allow increased expression of LEE and other adhesins, such as curli, without causing significant reductions in bacterial motility might explain the increased colonization of cattle intestines by the qseBC mutant of EHEC O157:H7.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…E. coli O157 primarily colonizes the mucosal epithelium at the RAJ [17], although it can be isolated from the gall bladder and along the gastrointestinal tract [18], [19]. More than 100 genes are involved in the colonization of the bovine intestine identified by genetic and biochemical analyses [20], including the E. coli O157 type III secretion system that enables the translocation of effector proteins into host cells and is required for colonization of cattle [21], [22], [23], [24], [25]. Besides the bacterial factors, environmental factors are believed to contribute to the prevalence of E. coli O157 in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…That motility and/or flagella might not be required for human virulence is suggested by the increased isolation of sorbitol-fermenting non-motile EHEC O157:NM strains from HUS patients in Germany that adhered at significantly higher levels to human colonic epithelial cells and expressed increased amounts of curli [16]. However, in a recent study we have demonstrated that a hha deletion mutant of EHEC O157:H7 expressing LEE at very high levels but showing reduced motility due to the reduced expression of the flagellar gene fliC failed to establish increased colonization of cattle intestines compared to the wild-type strain [17]. Despite unsettled role of motility in EHEC O157:H7 colonization of bovine intestines, there is increasing evidence that flagella might promote adherence of EHEC O157:H7 to the target sites in the large intestine.…”
Section: Introductionmentioning
confidence: 87%